Reversing transverse dunes: Modelling of airflow switching using 3D computational fluid dynamics - Jackson, Derek W.T.; Cooper, Andrew; Green, Andrew; Beyers, Meiring; Guisado-Pintado, Emilia; Wiles, Errol; Benallack, Keegan; Balme, Matt (Earth and planetary science letters, 2020)
•3D modelling shows shear stress clustering on transverse dunes with reversed winds.•Winds on long stoss slopes and steep lees have higher surface shear stress and flux.•Reversed winds result in almost 10% less aeolian flux.•Dune surface remoulds to smoother topography under reversed wind regimes.•Findings may be an useful analogue for Transverse Aeolian Ripples (TARs) on Mars. Airflow dynamics across dune surfaces are the primary agent of sediment transport and resulting dune migration movements. Using 3D computational fluid dynamic modelling, this study examined the behaviour of near surface airflow travelling over transverse (reversing) dunes on a beach system. Wind direction was modelled in two opposing directions (both perpendicular to dune crestline) to investigate surface alteration of flow on the dune topography. Surface shear stress, velocity streamlines and potential sediment flux were extracted from the modelling. The work shows that under SW winds the surface (under the configuration measured) underwent almost 10% more aeolian flux than with opposing NE winds of the same magnitude. Differences were also noted in the airflow behaviour with SW winds staying attached to the surface with less turbulence while NE winds had detached flow at dune crests with more localised turbulence. The work provides detailed insights into how 3D airflow behaviour is modified according to incident flow direction of reversing dune ridges and the resulting implications for their topographic modification. These dune types also provide interesting analogues for similarly scaled Transverse Aeolian Ridges found on Mars and the findings here provide important understanding of flow behaviour of such landforms and their potential movement.